Need Analysis of Virtual Laboratory for Vocational School Learning Practices During Covid-19 Pandemic - Bunyamin, Eskawati Musyarofah; Siregar, Eveline Siregar; Kusumawardani, Dwi Kusumawardani (Journal of Education Reseach and Evaluation, 2021)
During the COVID-19 pandemic, schools did not open face-to-face learning services. The Ministry of Education and Culture has issued a policy learning from Home (BDR) to support the principles of the Education Policy in the COVID-19 Pandemic that the health and safety of students, educators, education personnel, families, and the community is the top priority. However, learning in Vocational School (SMK) is mostly based on practice so that BDR activities cannot be implemented. One thing that is done to overcome this is that some practicum activities can be executed using multimedia known as virtual laboratories. This study aims to conduct a need analysis for the development of a virtual laboratory for vocational school learning practices in the Covid-19 Pandemic.  The development of this virtual laboratory is based on a product-oriented learning development approach and uses a model development of William W. Lee and Diana L. Owens. The needs analysis stage consists of a needs assessment and a front-end analysis. Needs analysis is carried out to gather data about gaps and needs as well profiles of students that can be used as a basis or reference in developing virtual laboratory at the next stage. Data collection was carried out by means of observation, interviews, and distributing questionnaires. The results showed that a virtual laboratory was needed to support practical learning for vocational students. During the Covid-19 pandemic, this virtual laboratory could be used to help students prepare themselves before entering the real laboratory.